DAMPAK PERAN ORANG TUA DAN GURU DALAM MENINGKATKAN KEMAMPUAN MEMBACA AWAL SISWA KELAS 1 SEKOLAH DASAR - Elfitriani; Firman; Desyandri (IICLS (Indonesian Institute for Corporate Learning and Studies), 2023)
Some students have difficulty recognizing words, understanding letter concepts, or capturing sound patterns. Developing strategies that can be adapted for various learning styles is crucial so that each student can better overcome the challenges of early reading learning. The aim of this research is to describe the impact of the role of parents and teachers in improving the initial reading skills of grade 1 students at SDN 11 Lubuk Buaya Koto Tangah, Padang City. This research can adopt a qualitative approach through in-depth interviews with parents and teachers of grade 1 students at SDN 11 Lubuk Buaya Koto Tangah, Padang City. And classroom observations can also be carried out to directly understand teacher interactions with students and how the classroom environment supports reading learning. The research results found that the active involvement of parents and teachers had a significant positive impact on the development of children's early reading abilities. The role of parents is very important in forming a supportive learning environment at home, through reading together and providing positive stimuli for literacy. Meanwhile, teachers also have a big responsibility in providing quality reading education in the school environment. Keywords: Parents, Teachers, Early Reading ability